Dynamic modeling and identification of a reluctance synchronous machine parameters - Niewiara, Łukasz J.; Gierczyński, Michał; Tarczewski, Tomasz; Grzesiak, Lech M. (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
This article discusses an identification and modeling approach of a reluctance synchronous motor (RSM) based on the running rotor technique. The applied flux linkage approximation functions reflect the self-saturation and cross-saturation effects, and the applied mathematical model is continuous and differentiable. The proper design of the experiment is discussed, and relevant recommendations are made to ensure the mitigation of procedural mistakes in the experiments. A detailed analysis of the impact of configuration faults on the obtained experimental data is provided, considering distortions in the obtained flux linkage and inductance surfaces. Considering the achieved model accuracy, a novel model evaluation considering the achieved model accuracy technique based on transient current response is proposed.